The impact of academic burnout on academic achievement: a moderated chain mediation effect from the Stimulus-Organism-Response perspective - Qin, Zhenkai; Yang, Guifang; Lin, Ziqian; Ning, Yimin; Chen, Xiaolong; Zhang, Hongfeng; Un In Wong, Cora (Frontiers in Psychology, 2025)
ObjectiveWith the increasing academic pressure faced by university students, academic burnout has gradually become a critical factor affecting students' learning outcomes, drawing widespread attention in the field of education.MethodsA survey was conducted among 306 Chinese university students using five validated instruments: the Academic Burnout Scale, Learning Satisfaction Scale, Learning Engagement Scale, Academic Achievement Scale, and Educational Values Scale. Data were analyzed using SPSS 26.0 and PROCESS macro (Model 6 and Model 14), incorporating correlation analysis, regression analysis, mediation and moderated mediation tests via bootstrapping.ResultsAcademic burnout had a significant negative effect on academic achievement. Both learning satisfaction and learning engagement had significant positive effects on academic achievement and jointly played a chain mediation role between academic burnout and academic achievement. Educational values significantly moderated the effect of learning engagement on academic achievement, as well as the entire chain mediation pathway.DiscussionThe results highlight a significant chain mediation effect of learning satisfaction and engagement in the relationship between academic burnout and academic achievement. Moreover, educational values can significantly moderate the relationship between academic burnout and learning achievement. Based on the empirical findings, the study proposes three recommendations for improving students' learning achievements: Improve students' learning satisfaction; Strengthen the development of students' learning engagement; Enhance the positive influence of educational values. By addressing academic burnout from the perspectives of learning satisfaction, learning engagement, and educational values, the study aims to improve students' learning achievements and foster collaboration between schools, teachers, and students to create positive conditions for academic development.